Leisure constraints faced by elderly women: findings from a qualitative study among elderly women in Selangor - Minhat, Halimatus Sakdiah (Malaysian Public Health Specialist Association, 2014)
Women and elderly are often linked to several disadvantages and constraints in many aspects of life. The scenario could be even worse for an elderly woman. Participating in leisure has proven to be beneficial for elderly in general. Yet little is known about the pattern of leisure and constraints faced by elderly women in order for them to pursue leisure activities. This study aims to explore the various leisure constraints faced by the elderly women. A total of 20 elderly women were involved in this study, which were selected purposively and also by snowballing technique. An in-depth interview was conducted with each respondent lasted approximately 15 to 30 minutes. The identified constraints were categorized into three main themes, which were structural, intrapersonal and interpersonal constraints. Among factors that had been identified were preoccupation with domestic affairs, the unavailability of appropriate space or area to perform desired leisure activities, lack or unavailability of transportation, safety issue, misperceptions that being old should focus on religious activity and becoming effortless, domestic activities are comparable to exercise and lacking of elderly people to perform certain activities together. In view of the modifiable nature of most of constraints faced by the elderly women to pursue leisure activities, necessary actions should be taken by the relevant authorities in tackling the constraints and at the same time developing a more active and healthy elderly women society. The right of the elderly women and women in general should be acknowledged, including their desire to actively involve in certain leisure activities. They should also appropriately educate on the importance of leisure and involvement in other type of leisure activities other than religious activities.